Effect of coating element on joining stability of Sn-0.3Ag-0.7Cu solder joint due to aging test - Atiqah Mohd Afdzaluddin,; Maria Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Solder joint is important for providing mechanical support and functionality of electronic packaging. Established solder joint should be able to withstand in device service operation and the environment without significant changes in terms of their microstructural evolution and mechanical properties. This study investigates the effect of the coating element (Sn and Ni) on the joining stability of Sn-0.3Ag-0.7Cu solder joint. The solder joints were exposed to different aging test for 1000 h to observed microstructure and micromechanical properties changes. Microstructural observation by means of intermetallic compound layer thickness due to the aging temperature effect. Joining stability by means of micromechanical changes were studied using nanoindentation approach. It was found that the elastic behavior, reduced modulus, and hardness of Sn-0.3Ag-0.7Cu solder joint has reduced due to aging test. However, the plastic behavior of Sn-0.3Ag-0.7Cu solder joint has increased with the increase of the aging temperature. It is observed that the Ni coating has a significant effect and a more stable solder joint achieved. This can be evidenced from small changes in intermetallic compound layer thickness and micromechanical properties were achieved using Ni coating as compared to Sn coating after subjected to the aging test for 1000 h.